Can Daytime Transcranial Direct Current Stimulation Treatment Change the Sleep Electroencephalogram Complexity of REM Sleep in Depressed Patients? A Double-Blinded, Randomized, Placebo-Controlled Trial - Li, Zhe; Zhao, Xueli; Feng, Lingfang; Zhao, Yu; Pan, Wen; Liu, Ying; Yin, Ming; Yue, Yan; Fang, Xiaojia; Liu, Guorui; Gao, Shigeng; Zhang, Xiaobin; et al. (Frontiers in Psychiatry, 2022)
Study Objectives The purpose of this study was to determine the effects of daytime transcranial direct current stimulation (tDCS) on sleep electroencephalogram (EEG) in patients with depression. Methods The study was a double-blinded, randomized, controlled clinical trial. 37 patients diagnosed with a major depression were recruited; 19 patients(13 females and 6 males mean age 44.79±15.25 years) received tDCS active stimulation and 18 patients( 9 females and 9 males; mean age 43.61±11.89 years) received sham stimulation. Ten sessions of daytime tDCS were administered with the anode over F3 and the cathode over F4. Each session delivered a 2 mA current for 30 min per 10 working days. Hamilton-24 and Montgomery scales were used to assess the severity of depression, and polysomnography was used to assess sleep structure and EEG complexity. Eight intrinsic mode functions (IMFs) were computed from each EEG signal in a channel. The sample entropy of the cumulative sum of the IMFs were computed to acquire high-dimensional multi-scale complexity information of EEG signals. Results The complexity of REM EEG signals significantly decreased intrinsic multiscale entropy [iMSE] (1.732±0.057 vs. 1.605±0.046, P=0.0004 in the case of the C4 channel, IMF 1:4 and scale 7) after tDCS active stimulation. The complexity of the REM EEG signals significantly increased iMSE(1.464±0.101 vs 1.611±0.085, P=0.001 for C4 channel, IMF 1:4 and scale 7) after tDCS sham stimulation. There was no significant difference in the Hamilton-24 (P=0.988), Montgomery scale score (P=0.726), and sleep structure (N1%P=0.383; N2%P=0.716; N3%P=0.772) between the two groups after treatment. Conclusions Daytime tDCS changed the complexity of sleep in the REM stage, and presented as decreased intrinsic multiscale entropy, while no changes in sleep structure occurred. This finding indicated that daytime tDCS may be an effective method to improve sleep quality in depressed patients. Trial registration This trial has been registered at the ClinicalTrials.gov (protocol ID: TCHIRB-10409114, in progress).